The Effect of Cash Flow, Net Profit, And Dividend Policy on Stock Prices in Companies in The Jakarta Islamic Index (JII) : English - Cakrah, Yuyun Andira; Musmulyadi, M.; Syahriyah Semaun; Emily Nur Saidy (Manunggal Halim Jaya, 2025)
This study aims to analyze the effect of cash flow, net profit, and dividend policy on stock prices in the Jakarta Islamic Index (JII) companies from 2019 to 2023. The research method uses a quantitative approach with multiple regression analysis. The study results show that Cash Flow positively and significantly affects the Stock Price of companies listed in the Jakarta Islamic Index (JII) for 2019-2023. This is evidenced by the t-count value (2.389) > t-table (2.080) and the significance value of 0.026 < 0.05., Net Profit has been proven to positively and significantly influence the stock price. This conclusion is supported by the t-count value (2.603) > the t-table (2.080) with a significance of 0.016 < 0.05. The Spearman correlation also shows a strong positive relationship (0.712) with a significance of 0.000. The IV policy shows a positive and significant influence on the Stock Price, as evidenced by the t-count value (2,510) > t-table (2,080) and the significance of 0.020 < 0.05. The Spearman correlation showed a strong positive relationship (0.683) with a significance of 0.000. Moreover, simultaneously, the three independent variables significantly affected the Stock Price. This is shown by the value of F-count (18.147) > F-table (3.07) with a significance of 0.000 < 0.05. The coefficient of determination (R²) of 0.717 shows that the three independent variables can explain 71.7% of the stock price variation. In contrast, 28.3% is explained by other factors outside the research model that have satisfied all classical assumptions, including normality, multicollinearity, autocorrelation, and heteroscedasticity. The Chi-Square test also confirmed a significant relationship between all independent variables and the Stock Price. Thus, it can be concluded that this research model is valid and reliable in explaining the influence of cash flow, net profit, and dividend policy on stock prices in companies listed in the Jakarta Islamic Index (JII).